The feasibility of resistance in the workplace: A critical investigation - Hofmeyr, Benda (The Indo-Pacific journal of phenomenology, 2021)
In this article, I undertake a critical interrogation of the complex relations of control operating in the contemporary workplace of the knowledge worker by drawing on Foucault’s theorisation of power and resistance. I plot the risks to which the knowledge worker are exposed, the conditions of possibility as well as the challenges that complicate productive resistance in the workplace. In the process, I make use of an array of existing scholarly research that utilises the Foucauldian framework of the relationality of power and develops some Foucauldian concepts further and applies them to our present context.